Penambahan Fitur Tampilan LCD dan Micro SD Card Reader pada mesin Laser Engraver and Cutter di Laboratorium Pengemudian Listrik - Mochammad Darwis (UPT Laboratorium Terpadu, Universitas Diponegoro, 2020)
Laser engraver and cutter machine that have been made in previous research, can only be controlled by a computer. The addition of LCD display and Card Reader will make it work alone without using a computer (offline). Card reader is used to read gcode files from 2-dimensional design that have been made on a computer. LCD display is used to display a menu or a list of existing settings, the percentage of loading data from a gcode file and displays the 2-dimensional design of the gcode file. To move the menu on the LCD display an encoder switch is used. This additional feature was created using a microcontroller STM32F1 type as a core control system which performs serial communication with a laser machine. 32 bit ARM microcontroller is used because a lot of tasks has to perform. It must be able to read data from the SD card, display the image form from the gcode file and send it to the laser machine. Compared 3 types of gcode file of different file sizes and the speed of loading the data. The laser machine can perform its function by using the controls of the additional feature modules that have been made.